PENGEMBANGAN E-MODULE MATEMATIKA GAMIFIKASI BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR - SETYANINGRUM, INDAH DWI; DAMINTO, BAMBANG PRIYO; PURWANINGSIH, WHARYANTI IKA (E-Jurnal Matematika; Vol 12 No 3 (2023)DO - 10.24843/MTK.2023.v12.i03.p420, 2023)
This study aims to determine the development and feasibility of e-module gamification mathematics based on problem based learning to increase motivation to learn mathematics. This research uses the type of research and development (R&D). The model used is the ADDIE model. The stages of the ADDIE model are analysis, design, development, implementation, and evaluation. This research was conducted on 37 students at SMP Negeri 1 Sawangan. The results showed that e-module gamification mathematics based on problem based learning was very valid based on the average score of 4.5 for media experts and 4.3 for material experts. E-module gamification mathematics based on problem based learning meets the practicality criteria in a limited trial of 76.5% with good criteria and 82% in a broad trial with very good criteria. Meet the effectiveness criteria with an increase in the average learning motivation questionnaire before and after learning by 8.5% and student learning outcomes have increased as seen from the percentage of completeness pretest by 22.5% in the incomplete category and the percentage of completeness in the posttest by 77.4% in the complete category. e-module gamification mathematics based on problem based learning feasible to use if the criteria for validity, practicality, and effectiveness are met. In addition, students' learning motivation has increased after the use of e-module.